Coccidiosis in Broilers of Selected Commercial Farms in Taraba State, Nigeria - Tadawus, Rejoice Habila; Tutuwa, Jummai Adamu; David, Bando Christopher; Ogu, Emmanuel Odiba; Jesse, Polly Shingu; Haruna, Peace Gambo; Agbu, Tsoken Danji; Aigbogun, Blessing Smart (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Poultry coccidiosis has been reported as a major constraint to successful commercial and backyard poultry farming due to its significant high mortality rates and huge economic losses globally. This study was conducted to assess the prevalence of coccidiosis in broilers in commercial farms of Jalingo and Wukari Local Government Areas of Taraba State. A total of 500 faecal samples from droppings of broilers were randomly collected from the poultry farms in Jalingo and Wukari LGAs of Taraba State. The faecal samples were collected from the rectum of the chicken, using a disposable hand gloves and the ova in each faecal sample of broilers were detected by using floatation technique. A total of 80 birds, from both Local Governments were sacrificed for histopathological assay. Intestinal scrapes were also collected from various parts of the intestines (duodenum, jejunum, gizzard, ilium and the caeca) of freshly slaughtered chickens into clean petri dishes, and the samples were examined microscopically for the presence of oocysts. Data obtained were entered into Microsoft Excel and analyzed using the Statistical Package for Social Sciences (SPSS) program version 23. Out 500 faecal samples collected 81/500 (16.2%) were positive for coccidian ova across Jalingo and Wukari LGAs of Taraba State with a statistical significant difference of (χ2=5.477; P<0.05). Most of the infected broilers were in the age group 1-3 weeks and 4-6 weeks with a statistically non-significant difference of (χ2=3.305; P>0.05). Infection with Coccidian ova was found to be higher, 19.7% (50/250) in Wukari than in Jalingo. They had 12.1% (31/250). The prevalence of coccidiosis in the gastro-intestinal tract (GIT) of the slaughtered broilers showed that the Caecum had the highest prevalence of 62.5% (25/40) of oocyst while Ilium had the least 37.5% (15/40). The knowledge of the coccidiosis among farmers in Jalingo and Wukari LGAs showed that all of the (12/12) respondents or 100% have heard of the disease. Majority of the respondent 81.8% (9/12) knows about coccidiosis from the veterinary while a few respondent 19.2% (3/12) get to know about coccidiosis from their friends. The Seasonal occurrence of coccidiosis showed majority of the respondent 7/12 (58.3%) attributed the occurrence of coccidiosis to rainy season within the year while 41.7% (5/12) attributed it to anytime of the season. The knowledge of the occurrence of coccidiosis despite preventive measures among farmers showed that majority of the respondent 91.7% (11/12) had Coccidiosis on their farms before while few, 16.7% (2/12) have not had reoccurrence of the disease. The percentage response of respondents based on the poultry population per pen showed that Majority of the farmers 50.0% (6/12) had between 1-200 poultry population per pen on their farm while 25.0% (3/12) had between 201-500 poultry population per pen. Despite the fact that some numbers of the faecal materials examined during the course of this work were negative for oocysts at the time of collection, it is possible that some of these Broilers may be harbouring coccidia in the schizogonic or gametogonic stages of development at the time that the samples were collected. It is therefore necessary to design appropriate control strategies of coccidiosis in order to improve management of poultry birds in farms to boost poultry production in the part of the country.